Revolution of ID card / Belinda Michelle Benedict...[et.al] - Benedict, Belinda Michelle; Hasan, Muhammad Fazlee; Abdullah, Muhammad Nazir; Ab Rahman, Nur Aishah; Saha, Zukamirul (Faculty of Plantation and Agrotechnology, 2016)
Matric card act as identity for worker or student in any institution. But, matric card do not have various function to ease the task that need to be settle in short period. Here, in our company, we were specialized in production of matric card that also can act as smart card. We are also responsible in manufacturing the best smart card to be used in presentation which require the use of pen drive, pointer and controller. In this case, our smart card can be widely use in education, marketing and management field.